Analisis Kemampuan Membaca Nyaring Siswa Sekolah Dasar dalam Pembelajaran Bahasa Indonesia - Farida Nugrahani; Nuha Nisrina Putri; Wijayanti Wijayanti; Dibyo Laksono Susilo; Dwi Handayani; Yuni Susilowati; Sri Hartati (Lingua Franca, 2026)
Reading aloud is a fundamental language skill for primary school children, enabling them to comprehend and articulate written material. Preliminary observations in Grade V at Gawan 1 State Elementary School revealed variations among students in pronunciation, intonation, fluency, expression, and pausing during oral reading. This qualitative case study, conducted from May 5–19, 2026, involved 11 fifth-grade students and one classroom teacher. Data were gathered through observation, interviews, and documentation, then analyzed using Miles and Huberman's framework, which encompasses data reduction, presentation, and conclusion drawing. Validity was ensured through method triangulation. The findings indicated that the overall reading-aloud ability of Grade V students was satisfactory. Among the 11 participants, two demonstrated excellent performance, five achieved good results, three fell into the less category, and one was classified as very less. Pronunciation and fluency emerged as the strongest aspects, whereas intonation, expression, and pausing still needed refinement. Interview results suggested that reading habits and self-confidence significantly affect students' oral reading performance. These findings suggest that consistent reading practice should be incorporated into Indonesian language instruction to enhance students' reading skills more effectively.